The pathogenesis of PANDAS syndrome - controversies and consequences - a literature review - Helena Perenc; Marek Pędras; Karolina Pasieka; Karolina Majka; Kornelia Krawczyk; Michał Kosar; Paulina Kosiorowska; Urszula Korzonek; Kuba Kupniewski (Nicolaus Copernicus University in Toruń, 2024)
Introduction Pediatric autoimmune neuropsychiatric disorder associated with Streptococcal infections is a controversial topic. There are contradictory reports about some aspects of its etiology and pathogenesis. The aim of this study is to examine the nuance in the studies about the pathogenesis of PANDAS and to form conclusions about the consequences of these controversies regarding the possible treatment of this condition. Material and methods A PubMed and Google Scholar search was performed with specific keywords. Current state of knowledge The understanding of PANDAS became different over time. It was described both as a distinct disease and as a part of a broader spectrum - PANS. Many researchers have observed have shown no significant temporal relationship between Group A Streptococcal infection and the occurrence of PANDAS, while others have noted a clear link between GAS infections and increased risk of developing neuropsychiatric disorders. Elevated antistreptococcal antibodies were also observed in children with PANDAS diagnosis. There were also cases of tic disorders and OCD symptoms related to infections with pathogens different than GAS. Many researchers postulate that molecular mimicry is the mechanism by which the neuroinflammation develops. Anti-GAS antibodies produced during infections seem to target antigens of basal ganglia causing their malfunction, which would be consistent with the clinical presentation of the disease and which was proven by diagnostic imaging. Treatment options seem to target the pathogenesis of PANDAS well; however, their effectiveness is not consistently proven in different studies. Conclusions Although much is known about the pathophysiology of PANDAS, the targeted treatment is often not enough and there are no therapeutic protocols for the disease.